eMarketing - The Essential Guide to Online Marketing (Open textbook library., 2012)
eMarketing: The Essential Guide to Online Marketing is a textbook intended for third and fourth year marketing students and draws on both academic theory and practical experience. The book offers students information that is applicable to the eMarket industry by providing examples that are easily relatable. The book covers all of the important aspects of online marketing, including the areas associated with search engine marketing, affiliate marketing, web analytics and conversion optimization, web development, online copywriting, online advertising, webPR, online reputation management, pay per click advertising, viral marketing, social media marketing, search engine optimization, eMarketing strategy, market research, mobile marketing, crowd sourcing, and customer relationship management. The book also features summaries, learning objectives and discussion points for each chapter, as well as, a glossary and index.